Diastereomeric salt crystallization of chiral molecules via sequential coupled‐Batch operation. Issue 2 (4th December 2018) - Simon, Melba; Wood, Barbara; Ferguson, Steven; Glennon, Brian; Jones, Roderick C.
Abstract : A novel process, sequential coupled‐batch diastereomeric crystallization is presented for the resolution of racemic mixtures. This strategy utilized a preferential crystallization of diastereomeric salt followed by sequential coupled diastereomeric salt resolution of racemic ibuprofen with the resolving agent (S)‐lysine utilizing a novel small scale pneumatic liquid exchange design to couple two batch crystallizers. Results were compared to conventional sequential resolution via seeded isothermal batch crystallization. Diastereomeric salt resolution was developed using the ternary phase diagram of the isolated (R)‐ibuprofen‐(S)‐lysine and (S)‐ibuprofen‐(S)‐lysine salts and optimized empirically with the aid of process analytical technology. Sequential coupled‐batch crystallization was found to be capable of increasing the yield of both salts while maintaining purity. This gave an increase in both the productivity and yield (20.5% for (S)‐ibuprofen‐(S)‐lysine) compared to the equivalent sequential batch (17.7% for (S)‐ibuprofen‐(S)‐lysine) crystallization methodology. Single crystals of the (S)‐ibuprofen‐(S)‐lysine were isolated, and its single crystal structure determined. © 2018 American Institute of Chemical Engineers AIChE J, 65: 604–616, 2019